2023
DOI: 10.1021/acs.nanolett.2c04220
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrahigh Efficiency Excitonic Micro-LED

Abstract: High efficiency micro-LEDs, with lateral dimensions as small as one micrometer, are desired for next-generation displays, virtual/augmented reality, and ultrahigh-speed optical interconnects. The efficiency of quantum well LEDs, however, is reduced to negligibly small values when scaled to such small dimensions. Here, we show such a fundamental challenge can be overcome by developing nanowire excitonic LEDs. Harnessing the large exciton oscillator strength of quantum-confined nanostructures, we demonstrate a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…A prepatterned N-polar GaN on a sapphire substrate was used for the growth. The detailed patterning process can be found in our previous publications. ,, The epitaxy initiates with a 500 nm long Si-doped GaN nanowire segment, followed by a short-period superlattice (SPSL) consisting of 4 pairs of InGaN/GaN (thicknesses ∼8 nm/8 nm) for the purpose of reducing dislocations and effective strain relaxation in the subsequent high indium composition InGaN active region epitaxy. The active region consists of a 25 nm thick InGaN segment that is enclosed by GaN barriers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A prepatterned N-polar GaN on a sapphire substrate was used for the growth. The detailed patterning process can be found in our previous publications. ,, The epitaxy initiates with a 500 nm long Si-doped GaN nanowire segment, followed by a short-period superlattice (SPSL) consisting of 4 pairs of InGaN/GaN (thicknesses ∼8 nm/8 nm) for the purpose of reducing dislocations and effective strain relaxation in the subsequent high indium composition InGaN active region epitaxy. The active region consists of a 25 nm thick InGaN segment that is enclosed by GaN barriers.…”
Section: Methodsmentioning
confidence: 99%
“…Figure d shows a representative low-magnification, high-angle annular dark-field (HAADF) image of the nanowire array, wherein each layer is indicated by the atomic-number-sensitive image contrast. It was observed that for the SPSL and the active region, the center region of the InGaN is incorporated on the polar c -plane, while the edge is on the semipolar plane, which can be attributed to the unique partial faceting toward the nanowire sidewalls during the initial GaN elongation. , The indium map of the InGaN active region, shown in Figure d, was collected by electron-dispersive spectroscopy (EDS). The estimated indium compositions from the c -plane and semipolar plane are around 33 and 40%, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 111 ] Pandey et al reported an ultrahigh efficiency nanowire excitonic LED in the submicron green light spectrum. [ 112 ] By utilizing the large exciton oscillator strength of quantum‐confined nanostructures, with an EQE of 25.2% and a WPE of 20.7%, which are the currently highest values known for the same size, providing an effective way to break the efficiency bottleneck of green LEDs. In addition, the insertion of AlGaN barriers in the QWs of nanowire LEDs enables the screening of the QCSE, which is realized by the transfer of free electrons into the QWs induced by polarization positive bond charges, thus effectively solving the problem of wavelength blueshift.…”
Section: D Nanostructuresmentioning
confidence: 99%
“…[ 113 ] Through optimization of the Mg doping within the nanowires, the plasma damage‐induced deleterious effect can be eliminated, resulting in a peak EQE and WPE of ≈8.3% and ≈4.6% for submicrometer red LEDs with an emission wavelength at ≈650 nm. [ 114 ] Remarkably, as the diameter of nanowires decreases, the lateral diffusion of In adatoms is significantly enhanced, resulting in an increase of In incorporation and longer emitting wavelengths. [ 115 ] This observation is crucial for the development of monolithically integrated full‐color micro‐LEDs, offering a new avenue toward the creation of ultrasmall and ultrahigh resolution displays, as shown in Figure 7b–d.…”
Section: D Nanostructuresmentioning
confidence: 99%